Carboxylic acids as anchoring components on aluminum oxide for the alignment relay technique of single-walled carbon nanotubes. (26th February 2021) - Snowdon, Monika R.; Wang, Shirley; Mashmoushi, Nour; Hopkins, Scott W.; Schipper, Derek J.
Abstract : We illustrate using a carboxylic acid anchoring component in the Alignment Relay Technique on silica and alumina surfaces. We present theoretical calculations on the interactions between the iptycenes' various pockets and the carbon nanotubes. Abstract : The alignment of semiconducting single-walled carbon nanotubes (SWCNTs) can contribute to faster, lighter, and more efficient transistors, but the process needs optimization for mass production. We have previously described an alignment relay technique (ART) to facilitate the simultaneous orientation, diameter, and length of SWCNTs when placed on a substrate surface. To expand ART's utility, compatibility with a broad range of surfaces needs to be achieved. Here, we report on the ineffectiveness of ART to work on Al2 O3 and we suggest that the molecular tweezer requires a carboxylic acid in order to bind to alumina. We tested the new carboxylic acid moiety with two liquid crystal solvents to improve alignment on silica, as well as on atomic layer deposited alumina and alpha-Al2 O3 substrates. We show that the carboxylic acid modification increased the SWCNTs' alignment on the Al2 O3 surface by 20% in relation to the first-generation ART molecule. We used quantum chemical calculations to explore nanotube interactions with the iptycene molecular tweezers. Our calculations indicate a significant preference for nanotube orientations in the binding pocket of the iptycene derivative. Our work optimizes the applicability of ART towards the deposition on a variety of substrates for electrical devices.